SURFACE CHARACTER OF IRON OXIDE/CARBON NANOPARTICLES SYNTHESIZED BY SUBMERGED ARC DISCHARGE METHOD IN ETHANOL/UREA MEDIUM - Saraswati, Teguh Endah; Sari, Fitri Nela; Handayani, Nestri (ALCHEMY Jurnal Penelitian Kimia, 2017)
Synthesis of iron oxide nanoparticles modified with carbon has been successfully performed by submerged arc-discharge method in ethanol/urea medium. Iron oxide used in the fabrication process was prepared by iron electrolysis in an electrolyte solution of NaCl. Fabrication of nanoparticles in this method uses two graphite electrodes. One of them was made in a pointed shape and the other graphite electrodes hollowed out and filled with a mixture of iron oxide, graphite and glue silica (as binder) with a ratio of 1:3:1 (w/w/w). The liquid medium used in this method is a mixture solution of ethanol 50% and urea (0%, 10%, 25% and 50%) with a volume ratio of 1:1 (v/v). The crystalline of iron oxide was characterized using X-Ray Diffraction (XRD), compared to JCPDS No. 89-0597, No. 89-0691 and No. 39-1346. Variations in the urea concentration in the liquid medium provided the changes of the surface character of the synthesized nanoparticles. The changes of surface character were analyzed by the Fourier Transform Infra Red (FTIR) spectra and nanoparticle dispersion in water and ethanol. FTIR spectra showed the absorption of Fe-O, CH, CN, C = O, OH and NH at 460-555 cm-1, 650-1000 cm-1, 1000-1350 cm-1, 1640-1680 cm-1, 2400-3400 cm-1, 3200-3400 cm-1, 3100-3500 cm-1, respectively. The best hydrophilic surface character achieved when the nanoparticle was synthesized in medium of ethanol 50% with the addition of urea50%. The existence of a functional group attached on the surface of nanoparticles synthesized in ethanol/urea makes these nanoparticles had better dispersion than nanoparticles synthesized in ethanol medium without urea addition.